"Determinants of shopping centre preferences:Cali, Colombia" (2022)
The tendency to choose a shopping centre has motivated the interest in the development of this study, which aims to identify the factors of commercial attraction (place of residence, socio-economic level, transport system and reasons for visit) that determine preferences when going to a shopping centre. This study focuses on the five main shopping centre in the city of Cali, Colombia. Since most previous studies on this topic conducted in this region are limited to a qualitative scope, this study has a quantitative focus. Methodology: A survey of 516 people was carried out at consumers´ homes, and a generalised linear model with multinomial logit was adjusted. Findings: Socio-economic level, educational level, marital status, distance and leisure are determinants of visitors' shopping centre preferences. These results are expected to help the entrepreneurs across these businesses upon implementing marketing strategies that are targeted to specific market segments that allow the strengthening of their natural market and to attract a potential market. These findings could be used in other types of business, research and by academics in the retail and marketing research areas